Squaramide—Naphthalimide Conjugates as “Turn-On” Fluorescent Sensors for Bromide Through an Aggregation-Disaggregation Approach - Kumawat, Lokesh K.; Abogunrin, Anthony A.; Kickham, Michelle; Pardeshi, Jyotsna; Fenelon, Orla; Schroeder, Martina; Elmes, Robert B. P. (Frontiers in Chemistry, 2019)
The syntheses of two new squaramide-naphthalimide conjugates (SQ1 and SQ2) are reported where both compounds have been shown to act as selective fluorescence “turn on” probes for bromide in aqueous DMSO solution through a disaggregation induced response. SQ1 and SQ2 displayed a large degree of self-aggregation in aqueous solution that is disrupted at increased temperature as studied by 1H NMR and Scanning Electron Microscopy (SEM). Moreover, the fluorescence behavior of both receptors was shown to be highly dependent upon the aggregation state and increasing temperature gave rise to a significant increase in fluorescence intensity. Moreover, this disaggregation induced emission (DIE) response was exploited for the selective recognition of certain halides, where the receptors gave rise to distinct responses related to the interaction of the various halide anions with the receptors. Addition of F− rendered both compounds non-emissive; thought to be due to a deprotonation event while, surprisingly, Br− resulted in a dramatic 500–600% fluorescence enhancement thought to be due to a disruption of compound aggregation and allowing the monomeric receptors to dominate in solution. Furthermore, optical sensing parameters such as limits of detection and binding constant of probes were also measured toward the various halides (F−, Cl−, Br−, and I−) where both SQ1 and SQ2 were found to sense halides with adequate sensitivity to measure μM levels of halide contamination. Finally, initial studies in a human cell line were also conducted where it was observed that both compounds are capable of being taken up by HeLa cells, exhibiting intracellular fluorescence as measured by both confocal microscopy and flow cytometry. Finally, using flow cytometry we were also able to show that cells treated with NaBr exhibited a demonstrable spectroscopic response when treated with either SQ1 or SQ2.